Future-oriented cognition: links to mental health problems and mental wellbeing in preschool-aged and primary-school-aged children - Marks, Jessica; Schneider, Silvia; Voigt, Babett (Frontiers in Psychology, 2023)
Future-oriented cognition plays a manifold role for adults' mental health. The present study aimed to investigate the relationship between future-oriented cognition and mental health in N = 191 children aged between 3 and 7 years. Parents completed an online-questionnaire including children's future-oriented cognition (e.g., episodic foresight; Children Future Thinking Questionnaire; CFTQ), children's mental health problems (Strengths and Difficulties Questionnaire; SDQ), and well-being (Parent-rated Life Orientation Test of children; PLOT and Positive-Mental-Health Scale; PMH).More externalizing problems (especially hyperactivity) related to lower future-oriented cognition. For mental well-being, higher levels of optimism were associated with higher episodic foresight. Future-oriented cognition increased with age cross-sectionally. This increase was flatter at higher levels of well-being (indicated by lower pessimism). Results are discussed considering findings on the role of future-oriented cognition for mental health in adults and adolescents. Suggestions for future work are presented regarding the direction of the observed links and underlying mechanisms.